2012
DOI: 10.1111/jeu.12007
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, Physiological, and Molecular Evidences Suggest that Euplotes parawoodruffi is a Junior Synonym of Euplotes woodruffi (Ciliophora, Euplotida)

Abstract: Euplotes woodruffi Gaw 1939 is a striking ciliate species commonly used in many fields of protistology. Euplotes parawoodruffi Song and Bradbury 1997 is separated from E. woodruffi by several morphological differences (e.g. the absence of pre-oral pouch) and in particular the brackish habitat (vs. freshwater). However, recent molecular data dispute the separation of E. woodruffi into two species. Based on a brackish isolate from the southeast of China, we investigated the morphology, molecular phylogeny, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Additionally, most species are found in freshwater habitats, although E. woodruffi and E. harpa live in brackish waters and E. encysticus inhabits fresh and brackish waters [26]. It has been demonstrated, however, that E. woodruffi is capable of salinity adaptation [57], which may have resulted in its separation from its ancestral lineage. The distinctly characteristic T-shaped macronucleus also supports the validity of E. woodruffi.…”
Section: (C) Taxonomic Controversy and Cryptic Species In Vannus-type Euplotes Speciesmentioning
confidence: 99%
“…Additionally, most species are found in freshwater habitats, although E. woodruffi and E. harpa live in brackish waters and E. encysticus inhabits fresh and brackish waters [26]. It has been demonstrated, however, that E. woodruffi is capable of salinity adaptation [57], which may have resulted in its separation from its ancestral lineage. The distinctly characteristic T-shaped macronucleus also supports the validity of E. woodruffi.…”
Section: (C) Taxonomic Controversy and Cryptic Species In Vannus-type Euplotes Speciesmentioning
confidence: 99%
“…Although their adaptation to brackish-water environment and the different lengths of the 2 arms of the T-shaped macronucleus suggest they could belong to the species E. parawoodruffi (Song & Bradbury 1997), this last species has been recently recognized as a junior synonym of E. woodruffi (Dai et al 2013). …”
Section: Discussionmentioning
confidence: 97%
“…Scale bars: 10 µm gene sequence was obtained (1832 bp, accession number HF548208). This sequence gave as the best hit on NCBI BLAST the E. woodruffi sequence JQ801447 (Dai et al 2013) with a similarity value of 100%. This result was confirmed by the similarity analysis performed on ARB: the sequence showed a range of similarity values between 99.7 and 100% with respect to 18S rRNA gene sequences of previously characterized E. woodruffi and E. parawoodruffi.…”
Section: Identification Of Host Ciliatementioning
confidence: 99%
“…However, since short time, referred to molecular data for E. woodruffi and E. parawoodruffi that cast doubt on the separation of the two species from each other. Dai, et al, (2013) isolated E. parawoodruffi and E. woodruffi from brackish waters and referred to E. parawoodruffi as a junior synonym for E. woodruffi. The 99 % sequence identity between the Mansoura's Nile species and both E. woodruffi and E. parawoodruffi indicated that our species is then E. woodruffi.…”
Section: Discussionmentioning
confidence: 99%